2019
DOI: 10.1038/s41598-019-47025-7
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterisation of fumarase C from a unicellular cyanobacterium demonstrating its substrate affinity, altered by an amino acid substitution

Abstract: The tricarboxylic acid cycle produces NADH for oxidative phosphorylation and fumarase [EC 4.2.1.2] is a critical enzyme in this cycle, catalysing the reversible conversion of fumarate and l- malate. Fumarase is applied to industrial l -malate production as a biocatalyst. l -malate is used in a wide range of industries such as food and beverage, pharmacy chemistry. Although the biochemical properties of fumarases have been studied in many orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…Synechocystis also encodes a succinyl-CoA synthetase complex (SucC/SucD), which probably catalyses the reversible conversion of succinate into succinyl-CoA in cyanobacteria [54], required for biosynthesis of methionine and lysine. Several recent papers have investigated the enzymatic properties of TCA enzymes conserved between cyanobacteria and heterotrophic bacteria [55][56][57]. In contrast with many heterotrophic bacteria, Synechocystis citrate synthase (GltA) was shown only to catalyse generation of citrate, not its cleavage.…”
Section: The Tricarboxylic Acid Cyclementioning
confidence: 99%
“…Synechocystis also encodes a succinyl-CoA synthetase complex (SucC/SucD), which probably catalyses the reversible conversion of succinate into succinyl-CoA in cyanobacteria [54], required for biosynthesis of methionine and lysine. Several recent papers have investigated the enzymatic properties of TCA enzymes conserved between cyanobacteria and heterotrophic bacteria [55][56][57]. In contrast with many heterotrophic bacteria, Synechocystis citrate synthase (GltA) was shown only to catalyse generation of citrate, not its cleavage.…”
Section: The Tricarboxylic Acid Cyclementioning
confidence: 99%
“…It is suggested that TeFum also becomes active at these growth temperatures. The optimum pH for CmFUM (pH 7.5 for fumarate hydration; pH 8.5 for l-malate dehydration) and TeFum (pH 7.0 for fumarate hydration; pH 7.5 for l-malate dehydration) were approximately the same as those of Class ІІ Fums from other organisms (pH 6.5-8.5, seven species: R. oryzae, Synechocystis 6803, Saccharomyces cerevisiae, S. solfataricus, C. glutamicum, A. thaliana, and Homo sapience; Puchegger et al, 1990;Keruchenko et al, 1992;Genda et al, 2006;Song et al, 2011;Zubimendi et al, 2018;Ajalla Aleixo et al, 2019;Katayama et al, 2019; Figures 2B,D). Intercellular pH of C. merolae and cyanobacteria is maintained near neutral where CmFUM and TeFum show enzymatic activities (Coleman and Colman, 1981;Zenvirth et al, 1985;Mangan et al, 2016).…”
Section: Discussionmentioning
confidence: 76%
“…Fums from A. thaliana (mitochondrial Fum;Zubimendi et al, 2018) and Synechocystis 6803 (Katayama et al, 2019), there was a significant difference between the optimum pH for fumarate hydration and l-malate dehydration in CmFUM and TeFum (particularly CmFUM; Figures 2B,D). Therefore, we can regulate the equilibrium of the reaction catalyzed by CmFUM by adjusting the pH.…”
mentioning
confidence: 98%
See 2 more Smart Citations